2014
DOI: 10.1007/s11250-014-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Santa Ines breed raised on pasture in semiarid tropical regions and factors that explain trait variation

Abstract: This study aimed to evaluate sex, the number of lambs per birth, and the family effects on production traits in the Santa Ines breed of sheep by estimating the least square means and coefficient of variance for those traits. A total of 484 lambs were evaluated for the following traits: weight at birth, at weaning, and at 240 days of age; weight gain during the pre-weaning and post-weaning periods; height, width, and length of different body regions; and rib eye area and fat thickness between the 12th and 13th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Santa Inês is the result of the intercurrent crossing in the northeast of Brazil between the genetic groups Bergamácia, Morada Nova, Rabo Largo, Somális, and other sheep without a defined racial pattern; it stands out for its productivity and rusticity, being biologically considered a new genetic material [18]. Male lambs of the Santa Inês breed show efficient growth parameters from 150 (extensive systems) to 250 (intensive systemsfeedlot) grams/day approximately [19,20]. In an intensive system, male Texel x Santa Inês crossbreed lambs showed a 65% difference in slaughter age (159 days-pasture vs. 263 days-feedlot) and 116% in average daily gain (0.133 g-pasture vs. 0.288 g-feedlot) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Santa Inês is the result of the intercurrent crossing in the northeast of Brazil between the genetic groups Bergamácia, Morada Nova, Rabo Largo, Somális, and other sheep without a defined racial pattern; it stands out for its productivity and rusticity, being biologically considered a new genetic material [18]. Male lambs of the Santa Inês breed show efficient growth parameters from 150 (extensive systems) to 250 (intensive systemsfeedlot) grams/day approximately [19,20]. In an intensive system, male Texel x Santa Inês crossbreed lambs showed a 65% difference in slaughter age (159 days-pasture vs. 263 days-feedlot) and 116% in average daily gain (0.133 g-pasture vs. 0.288 g-feedlot) [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, they were similar to the 17.7 kg described by Catto et al [ 22 ] in animals also weaned at 90 days with concentrate supplementation on Brachiaria grass pastures. In contrast to these findings, Farias Jucá et al [ 23 ] reported no significant differences in weaning weight based on birth type, but their study involved weaning at 112 days. This suggests that animals from twin births may exhibit compensatory gains when weaned at a later age.…”
Section: Discussionmentioning
confidence: 85%
“…The results of ultrasound measurements were lower than those found in the literature and can be considered low for the species. Jucá et al (2014) reported an average rib eye area of 6.45 cm 2 in Santa Ines sheep at 240 days, while Cartaxo et al (2009) evaluated the rib eye area of Santa Ines lambs and found averages of 20.4 kg and 7.53 cm 2 . However, in these studies the animals received supplemented diets, which increases the amount of protein and energy offered.…”
Section: Discussionmentioning
confidence: 99%